Mixed matrix membrane of poly(4-methyl-1-pentyne) and ZIF-8 for enhanced CO2 separation over H2 and CH4 - Behnam Majid-Nateri; Reza Abedini; Alireza Amiri (Scientific Reports)
Abstract Carbon dioxide (CO2) generally exists as the main impurity in natural gas, whose main component is methane. The presence of CO2 reduces the energy content of natural gas and also causes the corrosion of pipelines. To prevent such problems, natural gas must contain a small concentration of CO2 (less than 2% by weight). Membrane technology is an attractive separation method that has been widely studied due to its advantages such as high efficiency, low operating costs, and low energy requirements. However, in the last decade, Mixed Matrix Membranes (MMMs) have attracted the attention of many researchers due to their suitable capabilities in separating polar from non-polar gases. In this research, a new MMMs was obtained by adding imidazole zeolite nanoparticle (ZIF-8) to the poly methyl pentene (PMP) polymer matrix. The polymer part of this membrane can provide high permeability and suitable mechanical and thermal stability. In addition, ZIF-8 particles enhance CO2 separation by offering high CO2 adsorption capacity and molecular sieving, improving selectivity. The gas permeability test was performed on pure and mixed matrix membranes at 30 ℃ and pressures of 2, 6 and 10 bar. In addition, the fabricated membranes were evaluated by FESEM, FTIR-ATR, BET, DMA and TGA tests. The results indicated that in the MMMs containing 30 wt% of nanoparticles in the polymer, the permeability of CO2 gas improved by more than 180% and reached about 278.95 barrer, compared to the pure polymer membrane at a pressure of 10 bar. Moreover, the selectivity of CO₂/CH₄ and CO₂/H₂ increased by 142% and 155%, respectively, primarily due to the preferential sorption of CO₂ over H₂ and CH₄ facilitated by ZIF-8 particles.